A Lot of Progress, With More to Be Done: A Response to NIH Pathways to Prevention Report "Research Gaps for Long‐Term Drug Therapies for Osteoporotic Fracture Prevention". (25th July 2019) - Leder, Benjamin Z; Clarke, Bart L; Shane, Elizabeth; Khosla, Sundeep; Kiel, Douglas P
ABSTRACT: The public health implications of osteoporosis are enormous but the disease remains underdiagnosed and undertreated. In October 2018, the National Institutes of Health (NIH) convened a Pathways to Prevention (P2P) Workshop entitled "Appropriate Use of Drug Therapies for Osteoporotic Fracture Prevention" designed to identify research gaps, suggest future research opportunities, and advance the field through an evidence‐based assessment. By design, the P2P report focused on "gaps" in our knowledge base. Unfortunately, however, the report did not sufficiently acknowledge the current evidence that unequivocally demonstrates the therapeutic efficacy of existing pharmacologic therapies for osteoporosis, which has the potential to exacerbate the current crises in osteoporosis diagnosis and treatment. © 2019 American Society for Bone and Mineral Research.